3.0k views
3 votes
Simplify the below question.

Please send the answer with correct explanation.

Simplify the below question. Please send the answer with correct explanation.-example-1
User Tom Wyllie
by
5.3k points

2 Answers

4 votes

Answer:

48t^4

Explanation:

First you simplify and cross out all the uneeded characters because this is a division equation

Then whatever is left you calculate it

Simplify the below question. Please send the answer with correct explanation.-example-1
User Dimas
by
5.2k points
5 votes

Answer:


48t^(4)

Explanation:


(3^(3)*8t^(3)*32)/(9t^(-2)*16t)=(3^(3)*8*32*t^(3))/(9*16*t^(-2+1))\\\\=(3*1*32*t^(3))/(1*2*t^(-1))\\\\= (3*16*t^(3))/(t^(-1))\\\\= 48t^(3)*t^(1)\\\\= 48*t^(3+1)\\\\=48t^(4)

HINT:


a^(m)*a^(n)=a^(m+n)\\\\\\(1)/(a^(-m))=a^(m)

User Iamyogish
by
5.3k points